Proses Produksi Video Instagram Reels untuk Diseminasi Informasi Pemerintah: Studi Kasus @Diskominfobdg - Khalisah, Najmi; Suparman; Soelistiyowaty, Rr. Renny (Jurnal Indonesia : Manajemen Informatika dan Komunikasi, 2025)
This study aims to describe the Instagram Reels video production process by the Bandung City Communication and Informatics Agency (@diskominfobdg) in disseminating government information to the public. Using a descriptive qualitative approach, this study identified the production stages consisting of pre-production, production, and post-production. Data were obtained through in-depth interviews with three key informants directly involved in production, as well as observation and documentation during the period from January to May 2025. This study also revealed the obstacles faced by the production team and the efforts made to overcome these challenges. The results showed that each stage of production reflects the function of mass media according to Denis McQuail's theory, namely information, correlation, entertainment, and mobilization. The pre-production stage involves analyzing current issues, determining relevant topics, and compiling an interesting script. During production, visual aesthetics and technical aspects are considered to create interesting and informative content. Post-production focuses on editing, music selection, and scriptwriting to enhance the impact of the video. The Bandung Diskominfo team faced technical and human resource constraints, but managed to overcome them through collaborative strategies, efficient editing tools, and simplifying complex information. This study provides insight into the government's communication strategy in utilizing social media, especially Instagram Reels, as an effective and engaging means of disseminating information to the public while facing various challenges in the production process.